Labor flexibility and regional unemployment in Mexico: a panel cointegration analysis - Mendoza-Cota, Eduardo (Economía Sociedad y Territorio, 2016)
In order to corroborate the long-term effect of increasing temporary labor contract on the unemployment rate of the Mexican formal workers, a cointegration panel model was estimated. The results indicated the existence of panel cointegration of the series considered. They showed that causality goes from the unemployment rate and wages to the labor flexibility index. The estimations exhibited positive coefficients for the labor flexibility variable. It can be concluded that the evidence provided by the estimation ofthe model suggests that increasing labor flexibility increases the unemploymentrate but temporary labor contracts have had negative effects on that rate.